Chemical constituents and heavy metals contents of barley fodder produced under hydroponic system in GCC countries using tertiary treated sewage effluents - Isam Kadim, Yahia Othman, Asadullah Al Ajmi, Ahmed Ali Salih, (Journal of Phytology, 2009)
In this study, fodder barley was irrigated with pure tertiary treated sewage effluent (TTSE) and TTSE mixed with different amounts of tap water (20, 40, 60, and 80% tap water) using pure tap water as a check in a hydroponic system. The objective was to evaluate the effect of TTSE on heavy metals content (Pb, Cd and Ni) in barley biomass and some other nutrient elements (N, P, K, Ca and Fe). All these elements were present in much higher concentrations in TTSE compared to tap water. Heavy metal concentrations in barley biomass increased with an increase in the concentration of TTSE. Cadmium levels ranged between 0.06 (barley grown in tap water) and 0.1 ppm for barley grown in pure TTSE. These figures are lower than the limits set by the Commission of the European Union and WHO. Lead levels in biomass also increased with an increase in TTSE level. Ranging between 0.33 (tap water) to 0.7 (TTSE) ppm on dry weight basis, these levels are within acceptable limits for fodder. Nickel concentrations in barley biomass ranged between 6 (tap water) and 9 (TTSE) ppm. The toxic or excessive nickel concentrations in mature leaf tissue ranged between 10 to 100 ppm. The concentrations of N, P, K, Ca and Fe in barley biomass were within normal limits. The study revealed that fodder barley grown hydroponically could be irrigated safely with TTSE, as a useful alternative disposal method of waste water without the risk of accumulation of heavy metals in the soil.